STUDI LITERATUR DISTRIBUSI NORMAL DAN PENERAPANNYA DALAM PENELITIAN PENDIDIKAN - Harahap, Salsabila; Laila Alfi Sahri Lubis; Almira Amir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The normal distribution is a fundamental concept in statistics and serves as the basis for various parametric analytical techniques commonly used in educational research. It enables researchers to understand data patterns, assess student performance, and ensure the accuracy of analytical outcomes. This study employs a literature review by analyzing scientific sources related to the normal distribution, normality testing techniques, and their applications in educational research. The findings indicate that the normal distribution functions as a theoretical foundation, a tool for empirical data analysis, and an instructional medium through visualization. Several techniques—such as Shapiro–Wilk, Kolmogorov–Smirnov, and Anderson–Darling are applied to evaluate data suitability prior to further analysis. These results highlight the importance of normality assessment in ensuring the validity of research findings in education.